Effect of initial consolidation on the undrained shear response of cement treated soil - 180506 Md. Azman Md. Amin; Ismail Bakar; Jusoh Besar; Conference on Deep Foundations and Ground Improvement Schemes (1994 : Bangkok, Thailand)
08